Nutrition and physical activity (and other questions) - Nelson Nardo Júnior; Julio Tirapegui (Journal of Physical Education (Maringá), 2008)
Nutrition and Physical Activity themes have been used together for a long time as the essential elements for both health and performance, so they are often used by Physical Education professionals. On one hand it is possible to admit that major interests have been concentrated in ergogenic effects of some nutritional components. On the other hand, there are important considerations about the nutrition and physical activity interaction, especially concerning the pathological problems prevention and health maintenance. More researches are necessary in this field to clarify the great changes provoked by the Westernization of global eating habits. Therefore, this article aims at increasing the reflections about the nutrition and physical activity roles as a condition to public health with focus on economics and psychological aspects.